Food science database - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Intemational Food Information Service (IFIS) and SilverPlatter have launched a new CD-ROM version of Food Science Technology Abstracts (FSTA). FSTA on CD-ROM, which contains over 380,000 abstracts from 1969 to December 1990, will be searchable...